(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the study of the place and connections of legal culture in the general cultural system, revealing its national and universal aspects, and understanding its socio-political significance are highlighted on the basis of analytical ideas.